The role of fat-soluble vitamins on bone metabolism and osteoporosis: a literature review - Hongyang Li; Wenhai Cao; Lin Tao; Yue Zhu (Annals of Medicine, 2025)
Purpose The purpose of this review is to discuss the role of fat-soluble vitamins in bone metabolism and explore whether there is a relationship between each fat-soluble vitamins in the occurrence and development of osteoporosis.Methods We selected several databases, including PubMed, PubMed Central (PMC), Embase, and Web of Science, as the primary sources for the search. Keywords closely related to the subject of this study, such as ‘osteoporosis’, ‘vitamin A’, ‘vitamin D’, ‘vitamin E’, ‘Vitamin K’, ‘ferroptosis’, ‘osteoblast’ and ‘osteoclast’, were used in the search. The search deadline is April 20, 2025. All included clinical studies were graded for critical analysis GRADE.Results Among 573 reviewed articles, 182 were included (52 met GRADE criteria: A=10, B=26, C=11, D=5; 130 N/A). Vitamins D and K enhance osteoblast differentiation via RUNX2/ALP upregulation. Vitamin A’s bone effects remain debated, potentially interacting with vitamin D. Vitamins E and K may jointly regulate bone metabolism as ferroptosis inhibitors.Conclusion i Fat-soluble vitamins (D, K, E) may positively impact bone mineral density (BMD), while vitamin A’s effects remain controversial, potentially harming BMD at high doses. Current single-vitamin studies have limitations; future research should explore combined vitamin interactions to advance osteoporosis diagnosis and treatment.